Mobilidade forçada e exploração da força de trabalho : um olhar para os trabalhadores da cana-de-açúcar do noroeste paranaense - Ribeiro, Vitor Hugo (2011)
Even with the vast production about the migratory processes on the Brazilian territory, it's important to put some of the characteristics imposed by the capitalism way of production around these events. In this context, there is and attempt to contribute to some of the considerations about the rural worker linked to the agri-business of sugar cane, which has as a characteristic the migratory work. The formation of this workers occurred during the passing time, specially near the late XIX century and along the XX century. However there was a series of specific relations between several economic agents, such as the State, the capitalists and the farm owners (latifundiarios) that, with the intention of modernizing the activities in the Brazilian rural areas, promoted the peasants' expropriation through the constant modernization of the production techniques on the field, and with that started using free middle rural. This characteristic is similar to the Gaudemar's forced mobility theory (1976). For that, the northwest Paraná was marked out as study area for investigation of the mobility of the rural workers connected to the agri-business of sugar cane due to the remarkable increase of the sugar cane on that location that, with this increase of the sugar cane plantation besides the forced mobility of which the rural workers were submit, there is also the sugar expanding to the detriment of the mixed farming, very important to the local economy and the peasant family farming. Thereafter, three "municipal district" with high density of sugar cane were chosen, and there was an investigation on where the workers come from for the cutting of the sugar cane. The chosen municipal district were: Rondon, São Tomé and Cidade Gaucha. In all of them there are units of agri-business of sugar cane.